Extraction of Scandium and Iron from Red Mud. (2nd January 2022) - Wei, Ding; Jun-Hui, Xiao; Yang, Peng; Si-Yue, Shen; Tao, Chen; Kai, Zou; Zhen, Wang
ABSTRACT: Red mud as the main byproduct generated during alumina extraction from bauxite. Owing to the high iron content in the red mud and the high correlation between iron and scandium during the leaching process, it is necessary to extract the iron from the red mud and to further enrich the scandium in advance for the acid leaching extraction of scandium. In this research, the theory of red mud segregation roasting ore phase reconstruction is proposed, so that the iron and scandium in the red mud undergo a corresponding transformation, thereby achieving iron recovery in magnetic separation concentrate by magnetic separation, and enrichment of scandium in magnetic separation tailings. On this basis, the effects of temperature, leaching time, solid to liquid ratio and hydrochloric acid concentration on the leaching of scandium in magnetic separation tailings were studied optimal leaching process conditions and determine the leaching kinetics. A maximum Sc leaching efficiency of 83.94% was obtained at optimum leaching conditions of 200 rpm agitation speed, hydrochloric acid solution 20%, 80°C for 3 h, and solid/liquid ratios 1:10 (g/mL), −74 µm sample particle size. The process of leaching scandium with magnetic separation tailings conforms to the kinetic characteristics of multiphase liquid-solid region reaction, the apparent activation energy of scandium is 26.77 kJ/mol, and the leaching efficiency of scandium is controlled by the chemical reaction step.